2021
DOI: 10.3390/ijerph18084376
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Antibody Screening in Healthcare Workers in Non-Infectious Hospitals in Two Different Regions of Southern Poland (Upper Silesia and Opole Voivodeships): A Prospective Cohort Study

Abstract: (1) Background: Detection of asymptomatic or subclinical human coronavirus SARS-CoV-2 infection in healthcare workers (HCWs) is crucial for understanding the overall prevalence of the new coronavirus and its infection potential in public (non-infectious) healthcare units with emergency wards. (2) Methods: We evaluated the host serologic responses, measured with semi-quantitative ELISA tests (IgA, IgG, IgM abs) in sera of 90 individuals in Hospital no. 4 in Bytom, 84 HCWs in the University Hospital in Opole and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
1
9
1
Order By: Relevance
“…It is important to know that 25.5% of seropositive HCWs were never tested for infection. Similar results are reported by other studies done on HCWs [27,28]. Asymptomatic individuals also labeled as super spreaders of infection pose a tremendous challenge in the containment of transmission of SARS-CoV-2 infection in the present pandemic in all settings [29].…”
Section: Plos Onesupporting
confidence: 89%
“…It is important to know that 25.5% of seropositive HCWs were never tested for infection. Similar results are reported by other studies done on HCWs [27,28]. Asymptomatic individuals also labeled as super spreaders of infection pose a tremendous challenge in the containment of transmission of SARS-CoV-2 infection in the present pandemic in all settings [29].…”
Section: Plos Onesupporting
confidence: 89%
“…The local diversity observed varied between 1.2% and 10% (Opole vs. Bytom, p < 0.05; all without any symptoms). IgA seropositivity in HCWs was 8.8% in Opole and 7.14% in Bytom [ 24 ]. In the study carried out in Poznań (Poland) after the first wave of COVID-19 (July-September 2020), based on the ELISA results, it was found that 1.67% (95%CI 1.13–2.45) had antibodies against SARS-CoV-2 [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…100.00% of samples were negative; therefore, the diagnostic utility of IgA and IgM antibodies was not confirmed. It is worth noting that in abovementioned study, all positive IgM or IgA sera were collected from asymptomatic HCWs [12]. In other studies, the correlation between IgA serum concentration and severity of SARS-CoV-2 RNA positive was observed.…”
Section: Diagnostic Methods Of Sars-cov-2 Detectionmentioning
confidence: 75%
“…On the other hand, Bułdak et al, in their work revealed no statistical significance between positive antibody outcomes and symptoms. To increase the credibility of the outcomes in this research and avoid potential "serological window", the blood was drawn twice [12]. It should be noted that in Bułdak et al's work, reagents were more immunogenic (S1 domain) than in study by Huang et.…”
Section: Diagnostic Methods Of Sars-cov-2 Detectionmentioning
confidence: 99%